(untitled) (Comparative Professional Pedagogy, 2023)
The article is dedicated to the world experience of training teachers to work with migrant students from the point of view of teachers’ readiness for cultural diversity in the classroom. A review of English-language scientific and pedagogical literature related to teachers’ training to work in polyethnic classes of migrant students is carried out. Main directions of scientific research on this issue are determined: the study of peculiarities of migrant students’ education; analysis of challenges faced by teachers in culturally diverse classrooms; outlining positive changes in teachers’ training to deal with cultural diversity. The definition of the term “cultural diversity” in UNESCO documents is given and the essence of the term in the educational context is defined as the proper interaction of a teacher with other employees and students regardless of their ethnicity, race, gender, sexual orientation, age, physical features, socio-economic status and mental abilities. It is found that in order to effectively work with migrant students, a teacher must possess general pedagogical skills and abilities (communication and listening, creativity and ability to solve problems), as well as specific knowledge and skills (cultural anthropology, social psychology, cognitive development of students, integrated learning content and language, learning a second language). Some educational programs that train teachers to work in a polyethnic environment are analyzed and characterized according to the selected criteria (goal, target category, and providers). Based on the results of world experience analysis, a number of recommendations were outlined for improving the training of domestic teachers working within cultural diversity. They presuppose including certain issues of cross-cultural training into existing curricula and courses; developing separate educational programs for training teachers to work in a multi-ethnic classroom environment; providing appropriate educational and methodological support for cross-cultural training; optimal combination of theoretical and practical training of teachers; active use of innovative methods and digital technologies in the educational process. Prospects for further research include comparative pedagogical studies of educational policies of states that provide asylum and support to migrants, as well as research on professional development programs for teachers who work with school-age migrant students or adult students.